Standardized pulmonary vein isolation workflow to enclose veins with contiguous lesions: the multicentre VISTAX trial. Issue 11 (3rd September 2020) - Duytschaever, Mattias; Vijgen, Johan; De Potter, Tom; Scherr, Daniel; Van Herendael, Hugo; Knecht, Sebastien; Kobza, Richard; Berte, Benjamin; Sandgaard, Niels; Albenque, Jean-Paul; Szeplaki, Gabor; Stevenhagen, Yorick Jeroen; et al.
Abstract: Aims: To evaluate the safety and effectiveness of pulmonary vein isolation in paroxysmal atrial fibrillation (PAF) using a standardized workflow aiming to enclose the veins with contiguous and optimized radiofrequency lesions. Methods and results: This multicentre, prospective, non-randomized study was conducted at 17 European sites. Pulmonary vein isolation was guided by VISITAG SURPOINT (VS target ≥550 on the anterior wall; ≥400 on the posterior wall) and intertag distance (≤6 mm). Atrial arrhythmia recurrence was stringently monitored with weekly and symptom-driven transtelephonic monitoring on top of standard-of-care monitoring (24-h Holter and 12-lead electrocardiogram at 3, 6, and 12 months follow-up). Three hundred and forty participants with drug refractory PAF were enrolled. Acute effectiveness (first-pass isolation proof to a 30-min wait period and adenosine challenge) was 82.4% [95% confidence interval (CI) 77.4–86.7%]. At 12-month follow-up, the rate of freedom from any documented atrial arrhythmia was 78.3% (95% CI 73.8–82.8%), while freedom from atrial arrhythmia by standard-of-care monitoring was 89.4% (95% CI 78.8–87.0%). Freedom fromrepeat ablations by the Kaplan–Meier analysis was 90.4% during 12 months of follow-up. Of the 34 patients with repeat ablations, 14 (41.2%) demonstrated full isolation of all pulmonary vein circles. Primary adverse event (PAE) rate was 3.6% (95% CI 1.9–6.3%). Conclusions: The VISTAX trial demonstrated that a standardized PAF ablation workflow aiming for contiguous lesions leads to low rates of PAEs, high acute first-pass isolation rates, and 12-month freedom from arrhythmias approaching 80%. Further research is needed to improve the reproducibility of the outcomes across a wider range of centres. Clinical trial registration: ClinicalTrials.gov, number NCT03062046, https://clinicaltrials.gov/ct2/show/NCT03062046 .